Association between serum concentration of 25-hydroxyvitamin D and the risk of hip arthroplasty for osteoarthritis: result from a prospective cohort study. Issue 12 (December 2015) - Hussain, S.M.; Daly, R.M.; Wang, Y.; Shaw, J.E.; Magliano, D.J.; Graves, S.; Ebeling, P.R.; Wluka, A.E.; Cicuttini, F.M.
Summary: Objectives: There is ongoing debate regarding the optimal serum concentrations of 25-hydroxy-vitamin D for musculoskeletal health, including osteoarthritis (OA). The aim of this prospective cohort study was to determine whether serum 25-hydroxy-vitamin D concentrations were associated with the risk of hip arthroplasty for OA. Design: This study examined 9135 participants from the Australian Diabetes, Obesity and Lifestyle Study who had serum 25-hydroxy-vitamin D measured in 1999–2000 and were aged ≥40 years at the commencement of arthroplasty data collection. The incidence of hip arthroplasty for OA during 2002–2011 was determined by linking cohort records to the Australian Orthopaedic Association National Joint Replacement Registry. Results: Over an average 9.1 (standard deviation (SD) 2.7) years of follow-up, 201 hip arthroplasties for OA were identified (males n = 90; females n = 111). In males, a one-standard-deviation increase in 25-hydroxy-vitamin D was associated with a 25% increased incidence (HR 1.25, 95% CI 1.02–1.56), with a dose response relationship evident by quartiles of 25-hydroxy-vitamin D concentration ( P for trend 0.04). These results were independent of age, body mass index (BMI), ethnicity, smoking status, physical activity, season of blood collection, latitude, hypertension and diabetes, area level disadvantage or after excluding those with extreme low 25-hydroxy-vitamin D concentrations. No significant association was observed in women (HR 1.10, 95% CI 0.87, 1.39). Conclusions: Increasing serum 25-hydroxy-vitamin D concentrations were associated with an increased risk of hip arthroplasty for OA in males, while no significant association was observed in females. The mechanism for the association warrants further investigation.